The Living Qur’an Jar (TLQ Jar) sebagai Media Tadabbur: Studi Living Qur’an di Pesantren Al-Mawaddah - Ummi Qoni'atur Rohmah; Abd. Basid (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study is grounded in the phenomenon of declining depth in Muslim engagement with the Qur’an, which is often practiced in a ritualistic manner without meaningful reflection or internalization. In response to this gap, this study aims to analyze the implementation of The Living Qur’an Jar (TLQ Jar) as an innovative reflective medium within the Living Qur’an framework to understand the process of internalizing Qur’anic meanings in personal religious experiences in the digital age. This study employs a qualitative approach with a phenomenological paradigm to explore users’ subjective experiences in interpreting verses, reflections, and practical actions mediated by the TLQ Jar. Data were collected through participatory observation, in-depth interviews, and documentation within the santri community at Al-Mawaddah Pondok Pesantren Nurul Jadid Probolinggo and analyzed using the Miles and Huberman interactive model. The findings reveal that TLQ Jar functions as a reflective medium facilitating the internalization of Qur’anic values through three main structures: verses, reflective insights, and practical action guides. This interaction fosters emotional calmness, increased spiritual awareness, and integration of Qur’anic values into daily life. Reflective media based on personal and visual approaches are more adaptive to digital religiosity, although challenges remain, including inconsistent reflective practices and the potential simplification of meanings. Theoretically, this study extends the Living Qur’an discourse, while practically recommending strengthened interpretive guidance and technology-based reflective tadabbur models.